Morphology of seeds and seedlings of four species of Vigna Savi (Leguminosae, Phaseolinae) - Ojeda, Fabiana Soledad (2013)
Four neotropical species of Vigna Savi (Leguminosae, Phaseolinae) have potential value as forage crops or ornamentals and could be cultivated in tropical or subtropical areas, even on floodplains. In order to obtain useful data for their culture and taxonomy, the seed morphology, germination pattern (hypogeal or epigeal) and seedling development were studied. The studied species belong to different sections of the genus: V. adenantha (G.F.W. Meyer) Maréchal, Mascherpa & Stainier (Sect. Leptospron); V. candida (Vell.) Maréchal, Mascherpa & Stainier (Sect. Sigmoidotropis); V. caracalla (L.) Verdc. (Sect. Caracallae) and V. luteola (Jacq.) Benth. (Sect. Vigna). The seeds were collected during fieldwork conducted in northwestern and northeastern Argentina. The qualitative and quantitative characters of the seeds were registered, after which they were sown. The development of the emerged seedlings was followed, first in a greenhouse and thereafter in open field. We recorded the type of germination, the thigmotropic movements of the hypocotyl and of the stem, seedling architecture and plant longevity. These traits allowed us to differentiate the species and construct an identification key that could be useful for agronomic or floricultural purposes. The data obtained partially support the current taxonomic treatment of the genus.